Analysis of heat transfer for laminar flow in concentric pipes - Da?tekin, Ihsan; Öztop, Hakan Fehmi (My University, 2000)
In this study, laminar flow and heat transfer in a circular pipe with an inner tube inserted was investigated numerically. For this reason, two-dimensional Navier-Stokes, continuity and energy equations were solved using a finite volume method and SIMPLEM algorithm which is new in the literature. In the solution of the finite difference equations, a non-staggered grid arrangement was used. The calculations were performed for Reynolds numbers of 100, 500 and 1000 and Prandtl numbers of 0,1, 0,7, 7 and 10. In the application of inner tube insertion; vorticity, streamline patterns, pressure distributions, velocity profiles, variation of local Nusselt number and heat transfer rates were calculated. Furthermore, the use of SIMPLEM algorithm was discussed.
Ic ice yerlestirilmis borularda laminer akista isi transferinin incelenmesi
Keywords: Concentric pipe; Finite volume; Heat transfer enhancement; Non-staggered grid